2019
DOI: 10.1007/s10753-019-01136-5
|View full text |Cite
|
Sign up to set email alerts
|

Phillyrin Relieves Lipopolysaccharide-Induced AKI by Protecting Against Glycocalyx Damage and Inhibiting Inflammatory Responses

Abstract: Damage to the integrity of heparin sulfate (HS) in the endothelial glycocalyx is an important factor of glomerular filtration barrier dysfunction, which is the basic pathological feature of acute kidney injury (AKI). AKI is a common clinical critical illness with few drugs options offering effective treatment. Phillyrin (Phil), the main pharmacological component of Forsythia suspensa, possesses a wide range of pharmacological activities. However, the effects of Phil on lipopolysaccharide (LPS)-induced AKI have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…Vah. It has a wide range of pharmacological properties such as anti-inflammatory, antioxidation, and antiendotoxin effects [ 39 ]. Phillyrin produces good results in the clinical treatment of dry AMD, although its underlying mechanism has not been fully elucidated [ 40 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vah. It has a wide range of pharmacological properties such as anti-inflammatory, antioxidation, and antiendotoxin effects [ 39 ]. Phillyrin produces good results in the clinical treatment of dry AMD, although its underlying mechanism has not been fully elucidated [ 40 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…EG coats the luminal surface of glomerular capillaries, therefore its integrity is essential for glomerular filtration barrier function. Study in mice showed the protection against glycocalyx HS degradation is associated with reduction of LPS-induced AKI [ 27 ]. In addition, tests in mice demonstrated inhibition of the syndecan-4 shedding process attenuated diabetes-induced kidney injury in the early stage [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…2 E) ( Xia et al, 2010 ). Literature shows that phillyrin exhibits promising pharmacological properties against lung inflammation ( Zhong et al, 2013 ), traumatic brain injury ( Jiang et al, 2020 ) and acute kidney injury ( Zhang et al, 2020b ). Yang et al recently revealed that phillyrin could effectively inhibit the replication of SARS-CoV-2 in Vero E6 cells at an IC 50 of 63.90 μg/mL with a low toxicity profile (SI = 30.66) by inhibiting activation of the nuclear factor kappa B (NF-κB) signaling pathway ( Ma et al, 2020d ).…”
Section: Promising Active Ingredients Of Chinese Herbal Medicine Thatmentioning
confidence: 99%